An Analysis of Students’ Difficulties in Solving Matrix Problems in Mathematics Learning - Baiq Dwi Aini Safitri (Indonesian Journal of Educational Innovation, 2025)
This study was motivated by students’ low mathematical problem-solving abilities, particularly in matrix material that demands complex conceptual and procedural understanding. The purpose of this research is to analyze the types of difficulties students face in solving matrix problems and to identify their underlying causes. This qualitative research used a case study design, with data collected through observation, interviews, and document analysis involving eleventh-grade students at MA Nurul Qur’an Lendang Simbe. The results indicate three main types of learning obstacles: conceptual, psychological, and epistemological. Conceptual difficulties include misunderstandings of negative number operations and fundamental matrix concepts such as determinants and inverses. Psychological barriers arise from low learning motivation, such as reluctance to write out solution steps. Epistemological difficulties are shown by students’ inability to apply basic knowledge to complete problem-solving processes. The study concludes that difficulties in solving matrix problems are not merely due to weak formula mastery but are influenced by interconnected internal and external factors. Future research should involve more diverse participants, broader problem types, and teacher input to enhance instructional strategies.